The Effect of The Contextual Teaching and Learning (CTL) Model on Grade IV Students’ Science Learning Interest at SDN 133 Pekanbaru - Lusi Octaviana; Muhamad Nukman (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
This study examines the effect of the Contextual Teaching and Learning (CTL) model on students’ interest in learning Science and Social Studies (IPAS) in fourth grade at SD Negeri 133 Pekanbaru. This research employed a quantitative experimental approach with a one-group pre-test—post-test design. The population consists of 40 students, and all were selected as the sample using a saturated sampling technique. Data were collected using a Likert-scale questionnaire consisting of 20 items measuring students’ interest in learning. The questionnaire was administered twice, namely before treatment (pre-test) and after treatment (post-test), to determine changes in students’ learning interest after implementing the CTL model. Data analysis includes validity and reliability tests, a normality test using the Kolmogorov-Smirnov test, and hypothesis testing using a paired-samples t-test, with assistance from SPSS. The results indicate that all instrument items were valid and reliable, with a Cronbach’s Alpha value of 0.970. The normality test indicates that the data were normally distributed (Sig. = 0.200 > 0.05). The hypothesis test reveals a significant effect of the CTL model on students’ learning interest, with a significance value of 0.000 < 0.05. These findings underscore that the CTL model effectively enhances students’ engagement and interest by connecting learning materials to real-life contexts. This study contributes to the development of innovative and meaningful learning strategies in elementary education.